Primary Hypothyroidism with Markedly High Prolactin - Ansari, Mohd Saleem; Almalki, Mussa H. (Frontiers in Endocrinology, 2016)
Secondary Pituitary enlargement due to primary hypothyroidism is not a common manifestation. The loss of thyroxin feedback inhibition in primary hypothyroidism causes overproduction of thyroid-releasing hormone (TRH), which results in secondary pituitary enlargement.TRH has a weak stimulatory effect on lactotroph cells of pituitary, so mild to moderate rise in prolactin (PRL) level is expected. We report a 67 years old female who presented with a large pituitary mass and very high level of TSH with a significant rise in PRL level. In this case the diagnosis of seller mass was challenging, it was difficult to distinguish between pituitary prolactinoma and primary hypothyroidism with secondary pituitary hyperplasia. The thyroid hormone replacement proved that hyperprolactinemia was due to hyperplasia of the pituitary gland. Hence, the correct diagnosis and thyroid hormone therapy can prevent unnecessary treatment with dopamine agonist.